Analisis Survival Suhu Tubuh pada Pasien Pneumonia yang Diberikan Vitamin D - Arief Rafsanjani; Endang Darmawan; Nurcholid Umam Kurniawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Pneumonia is caused due to an infection in the lungs so antibiotics need to be administered for its management. Giving antibiotic combination therapy gives pretty good results in some cases, but the problem of mortality rates that occur is still high, it is necessary to be given additional therapy to increase the patient's cure rate. One of the adjuvant therapies that can be given is vitamin D. vitamin D is known to play a role in the body’s defense function, both in natural and adaptive immunity and plays a role in the body’s defense in cases of infections, allergies, malignancies, and autoimmune. This research was an experimental Double-Blind Randomized Clinical Trial. The study subjects were pediatric patients aged six months to 18 years who were divided into two groups, namely the intervention group (n = 35) and the control group (n = 35). The intervention group received vitamin D, while the control group received a placebo. Data observed were body temperature. This study aimed to determine the effectiveness of vitamin D based on the parameters of fever in pediatric patients with pneumonia infections treated at the Muhammadiyah Bantul Hospital. The results of this study prove that vitamin D is able to provide a chance of survival on the third day after the administration of vitamin D